Functional dyes - Kim, Sung-Hoon (Elsevier, 2006)
In the last 10 years organic dyes, traditionally used for coloring textiles and other materials, have become increasingly important in the hi-tech industries of electronics and optoelectronics. They can be used in optical data storage, new solar cells and biomedical sensors. Functional Dyes discusses the synthesis of these new, high-value dyes and pigments as well as their applications and performance. The chapters are arranged so that the reader logically advances from the fundamental concepts to more practical aspects of the technology in which they are used. In providing the reader with current information on functional dye chemistry, as well as important developments within the field, Functional Dyes is a valuable information source for dye and material chemists, researchers and graduates, who want a summary of the key advances in the field over the last 10 years and an authoritative view on future developments. * Provides a broad introduction to the science technology of the functional dye application * Reviews recent advances on synthesis and characteristics of the functional dyes and their applications * Is a valuable information source for dye and material chemists and researchers.
Keywords: Dyes and dyeing -- Chemistry.; elektronické knihy; electronic books